Adequate Reporting Among Ventral Hernia Repair Operative Reports: A Cross-Sectional Study of Prevalence of Details and Association With Clinical Outcomes - Said Maldonado, BS; Nicole B. Lyons, MD; Jonathan S. Lall, BS; J. Scott Zimmerle, MBA; Brendan Rosamond, BS; Ashlynn Mills, BS; Yoolim Alex Seo, BS; Angelica Calderon Rodriguez, BS; Rainna Coelho, MD; Natalia Cavagnaro, MD; Zuhair Ali, MD; Mike K. Liang, MD (Annals of Surgery Open)
Objective:. We aimed to evaluate the prevalence of highly detailed ventral hernia repair (VHR) operative reports and associations between operative report detail and postoperative outcomes in a medico-legal dataset. Background:. VHR are one of the most common surgical procedures performed in the United States. Previous work has shown that VHR operative reports are poorly detailed, however, the relationship between operative report detail and patient outcomes is unknown. Methods:. This is a retrospective cross-sectional observational study. Operative reports describing VHR were obtained from a medical-legal database. Medical records were screened and data was extracted including clinical outcomes, such as surgical site infection (SSI), hernia recurrence, and reoperation and the presence of key details in each report. Highly detailed operative reports were defined as having 70% of recommended details. The primary outcome was the prevalence of highly detailed VHR operative reports. Results:. A total of 1011 VHR operative reports dictated by 693 surgeons across 517 facilities in 50 states were included. Median duration of follow-up was 4.6 years after initial surgery. Only 35.7% of operative reports were highly detailed. More recent operative reports, cases with resident involvement, and contaminated procedures were more likely to be highly detailed (all P < 0.05). Compared to poorly detailed operative reports, cases with highly detailed reports had fewer SSIs (13.2% vs 7.5%, P = 0.006), hernia recurrence (65.8% vs 55.4%, P = 0.002), and reoperation (78.9% vs 62.6%, P = 0.001). Conclusions:. In this medico-legal dataset, most VHR operative reports are poorly detailed while highly detailed operative reports were associated with lower rates of complications. Future studies should examine a nationally representative dataset to validate our findings.